Single Joint Hybrid Assistive Limb (HAL-SJ) robotic exoskeleton therapy in improving functional outcomes among workers with wrist fractures: Study protocol for a randomized controlled trial - Eng Wah Tan; Siaw Chui Chai; Yoshiyuki Sankai; Masahiro Shingu; Nor Afifi Razaob; Hafez Hussain (PLoS ONE, 2025)
Introduction Robotic technologies have been developed for motor rehabilitation and such robots have shown favourable results when compared with equivalent doses of usual clinical therapy. Recently, robotic interventions have been suggested to be applied in orthopaedic rehabilitation with upper extremity disorders, especially those related to hand and wrist. This study aims to determine the effectiveness of combined conventional therapy and HAL-SJ robotic therapy in restoring the wrist functionality following the fractures as compared to the standard conventional therapy solely. Methods and analysis Workers with wrist fractures will be randomized in two groups, i.e., the control group (conventional therapy) and intervention group (combination of conventional therapy and robotic HAL-SJ intervention). All participants will receive 5-day/week therapy sessions for four weeks. Primary outcomes of the Disabilities of the Arm, Shoulder and Hand (DASH) outcome measure and secondary outcomes of range of motion, grip and pinch strengths, fine and gross hand dexterity as well as pain and the Lam Assessment of Stages of Employment Readiness (LASER) will be assessed at baseline assessment and upon completion of the therapy program after 4 weeks. Data from the baseline and post intervention outcome measures will be analysed using a Repeated Measures ANOVA to compare the therapy effectiveness of both control and intervention groups. Results Participants recruitment and data collection are in progress Discussion Wrist fractures can produce some residual disability and pain that may impact the functionality of a person. The application of robotic technology in facilitating upper limb movement and functional recovery training is extensive and shows positive outcomes in the field of neurorehabilitation. However, there is a lacking of published evidence about the effectiveness of robotic intervention in orthopaedic rehabilitation, especially in the field of hand therapy. Conclusion Participants recruitment and data collection are still ongoing Clinical trial registration This trial is registered with the Australian New Zealand Clinical Trials Registry (registration number: ACTRN12622000413729).